Blood pressure monitoring and outcomes-related hypertension in patients with migraine treated with erenumab: a systematic review and meya-analysis - Makita, Luana Miyahira; Koppanatham , Aishwarya; Corso, Angela Maria Sandini; Kojima, Giovana Schlichta Adriano; Neves, Henrique Alexsander Ferreira; Kleimmann, Rafael de Freitas; Oliveira, Rafael Reis de; Alves, Vinícius Salles; Piovesan, Elcio Juliato (Headache Medicine, 2024)
INTRODUCTION: Erenumab is an anti-CGRP receptor antagonist approved for the preventive treatment of migraine. The US Prescribing Information for this medication was recently updated to include the risk of hypertension based on postmarketing data, although prior clinical evidence did not link erenumab use to adverse vascular events. Therefore, this association remains uncertain. OBJECTIVE: We performed a systematic review and single-arm meta-analysis to explore the relationship between erenumab and blood pressure variations in patients with migraine. METHODS: Embase, PubMed, and Cochrane databases were searched up to June 18 for studies evaluating the impact of initiation of erenumab on blood pressure (BP) in migraineurs. Records were screened by two independent reviewers using pre-determined eligibility criteria. Mean difference (MD) and incidence were computed using random-effects model. I2 statistics and prediction intervals (PI) were analyzed to assess heterogeneity. Sensitivity and subgroup analysis were used to explore the heterogeneity. RESULTS: Ten studies comprising 3.218 patients undergoing treatment with erenumab were included. Systolic (MD 0.86; P>0.05; I2 = 63%) and diastolic (MD 1.33; P>0.05; I2 = 69%) BP measures did not significantly differ between post- and pre-erenumab treatment. This lack persisted at 3 and 12 months. The leave-one-out technique did not change heterogeneity substantially. The proportion of participants presenting a worsening on BP appears to be 21.9% (PI 0.93, 89.37), with 56.1% corresponding to non-hypertensive individuals at baseline. The incidence of patients starting antihypertensive medications during the study was 3.7% (PI 0.04, 79.52), with 63% being non-hypertensive patients. CONCLUSION: We did not find an association of erenumab with an increased BP. Regarding clinical significance, the incidence of patients initiating antihypertensive treatment seems to be low. There is a significant degree of fragility in the current evidence available. The decision to prescribe erenumab or not, especially for patients with multiple comorbidities and risk factors for hypertension, must be made with the multidisciplinary team and weighing up the risks and benefits. Further studies are needed to confirm this association.